Dupont System Analysis in Measuring The Financial Performance of PT. Antam Tbk Pre and Post Bullion Bank - Saputra, Bayu Akbar; Faizah, Iva; Carmidah (Universitas Islam Negeri Raden Intan, 2025)
Changes in the dynamics of the national gold industry and the implementation of the Bullion Bank policy require an evaluation of the financial performance of mining companies, particularly PT Aneka Tambang Tbk as a strategic state-owned enterprise in the precious metals sector. This study examines the financial performance of PT Aneka Tambang Tbk before and after the implementation of the Bullion Bank policy using the DuPont System approach. The analysis focuses on Net Profit Margin, Total Asset Turnover, Equity Multiplier, and Return on Equity, based on secondary data from the company’s financial reports for the first to third quarters of 2024 and 2025. The results show improvements in all DuPont ratios after the policy implementation, primarily driven by more effective asset utilization. However, these ratios remain below industry standards, indicating that the company’s financial performance has not yet reached an optimal level. This study contributes to financial management literature by providing empirical evidence on the impact of the Bullion Bank policy on the performance of gold mining companies. Keywords: Financial Performance, DuPont System, PT ANTAM Tbk, Bullion Bank